A STUDY OF THE CONSIDERATION GIVEN COLOR IN ELEMENTARY SCIENCE PROGRAMS. - Schaeffer, Maud (Science Education, 1940)
The article presents information on a study which concentrates on the role of the teaching of color in elementary schools. The Kindergarten and the first six grades has made a consideration to the study of color. It has been found that the study of color in elementary schools seems to have been limited to courses in Art, with few exceptions. Commerce and Art have multiplied color possibilities in scientific developments. Color has emerged as an intangible concept, and its use concerns all individuals, in all phases of living. Color is treated in a superficial manner in most elementary science texts. It has been found from some elementary school programs related to nature study that only a few of the larger city school systems include color study in elementary science education. These schools build up a definite progressive color study through the grades.